Simultaneous coronary artery bypass and carotid endarterectomy. Determinants of outcome. - Vassilidze, T V (1994)
From January of 1988 to May of 1993, simultaneous single-stage coronary revascularization and carotid endarterectomy was performed in 33 patients (mean age, 69 years). Thirty-one patients (94%) were in New York Heart Association class III or IV, 15 (46%) had unstable angina, and 7 (21%) were operated on because of evolving myocardial infarction. One or more previous myocardial infarctions were present in 18 patients (54%). Nineteen patients (58%) presented with neurologic symptoms, and 22 (67%) had severe bilateral carotid stenosis. Thirty (91%) had triple-vessel or left main coronary artery disease. Sequential reconstruction of the carotid artery followed by coronary artery bypass grafting was performed in all patients. In 4 cases, additional cardiac procedures were performed. Operative mortality (6%) was cardiac related. Perioperative morbidity included myocardial infarction in 1 patient (3%) and neurologic deficit in 6 (18%), with permanent functional impairment in 2 patients (6%). The stroke rate was higher in the bilateral than in the unilateral carotid stenosis group (22.7% vs 9.1%, p = 0.047). Previously completed stroke influenced the operative outcome (55.6% vs 4.2%, p = 0.003). Low ejection fraction (33.5% +/- 7.5% vs 52.8% +/- 3.5%, p = 0.03) and left main coronary artery disease (36% vs 5%, p = 0.03) also predicted postoperative neurologic complications. During a mean follow-up of 24.6 +/- 3.5 months, 3 patients died. The 5-year life-table survival rate was 85%. Eighty-nine percent of long-term survivors were free of cardiovascular disease symptoms. Our results show that the out come of simultaneous carotid endarterectomy/coronary artery bypass grafting in this high-risk population depends upon the preoperative absence or presence of completed stroke or bilateral carotid stenosis, upon the preoperative ejection fraction, and upon the extent of the left main coronary artery disease.